Empowerment of Plural Societies: Educational Contribution of the Annuriyyah Islamic Boarding School Kaliwining Rambipuji Jember City - Hasanah, Siti Muflihatul; ., Misnawar; Khoirul, Mohamad (MAJEMUK Jurnal Pendidikan Agama Islam, 2024)
Basically, education is the main means in efforts to improve the quality of human resources, like an experiment that will never be finished, as long as there is human life in this world. It is said that because education is part of human culture and civilization which continues to develop to provide goodness to the plurality of society. The approach used in this research is qualitative research. The technique used by this researcher is purposive sampling technique. data collection using observation methods, interview and documentation methods, the technical analysis used is qualitative. The results of this research are that the Annuriyyah Islamic boarding school is developing a pluralistic society by using several approaches to establish (1) Kindergarten, MI, MTs and MA level schools for the general public. (2) non-formal education, namely Madrasah Diniyah, Kuning Book Recitation and Majlis Ta'lim. (3) empowering the economy of a pluralistic society with trade routes and establishing the Annuriyyah cooperative (4) strengthening community culture by strengthening morals, mastering religious knowledge and carrying out community activities: joint istighasah and providing support for orphans and the poor.